The Essential Pocket Guide for Clinical Nutrition - Width, Mary; Reinhard, Tonia (Burlington, MA : Jones & Bartlett Learning, 2025)
"The Essential Pocket Guide for Clinical Nutrition is a quick-reference guide for dietitians, students, and other health professionals actively engaged in clinical nutrition, providing them with immediate access to evidence-based information on nutritional assessment, nutrition support, and nutrition considerations for specific diseases such as cancer, cardiovascular disease, diabetes, and pulmonary disease. Using the latest nutritional guidelines, the authors utilize a consistent chapter format that includes sections on disease process, treatment and nutritional intervention, and patient education, making it easy to find relevant information"--
Nutrition Assessment -- Pregnancy -- Assessing Pediatric Patients -- Long-term Care and the Older Adult -- Nutrition Support -- Bariatric Surgery -- Cancer -- Cardiovascular Disease -- Diabetes -- Gastrointestinal Disease -- Hepatobiliary Disease -- Kidney Disease -- Pulmonary Disease.
Includes bibliographical references and index.
Keywords: Nutrition Assessment; Dietetics -- methods; Nutrition Therapy; Nutritional Physiological Phenomena; Handbook